FORMULA MAKING MATHEMATICAL VISUALIZATION AND EXERCISE ROOM AND CONSTRUCTION PROBLEMS USING MICROSOFT VISUAL BASIC INTERACTIVE 6.0 - Putri Soraya; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2006)
In the current era of globalization developments in science, technology and information increasingly fast and sophisticated. Many all fields associated with a computer because with a variety of computer knowledge can be searched here. With the convenience to gain that knowledge then the authors are interested in creating applications using the mathematical formula set  Ms Visual Basic 6.0. This application is made to meet the needs of the learning process for students because the authors saw the students is still very difficult to learn much less to memorize formulas built up such a formula other than that they were also hit by the existing curriculum so that did not have time to explore and understand more about the formula up  mathematics, using electronic media, the author hopes they can better understand mathematical formula wake up and no longer considered the scourge to be feared.